2011
DOI: 10.1016/j.hlc.2011.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Primary Care Management of Hypertension: The Valsartan Intensified Primary Care Reduction of Blood Pressure (VIPER-BP) Study

Abstract: Background: Intra-arterial Doppler is a novel technique which enables accurate assessment of blood flow haemodynamics. We evaluated the feasibility of using intra-arterial Doppler for insights into the pulmonary artery flow velocity profile in patients with pulmonary arterial hypertension (PAH), and determined the changes in the flow velocity profile following pulmonary vasodilator therapy.Methods: Intra-arterial Doppler was performed in the pulmonary arteries of seven subjects with PAH before and after six mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As described in our previous reports describing the rationale and design of the study and the primary results in favor of the study intervention of more intensive primary care management overall, the VIPER‐BP study was a pragmatic, multicenter randomized controlled trial involving a total of 119 general practices Australia‐wide. The study received ethics approval from all relevant bodies including the Alfred Hospital Ethics of Human Research Committee, Melbourne, Australia, in accordance with the Declaration of Helsinki (2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our previous reports describing the rationale and design of the study and the primary results in favor of the study intervention of more intensive primary care management overall, the VIPER‐BP study was a pragmatic, multicenter randomized controlled trial involving a total of 119 general practices Australia‐wide. The study received ethics approval from all relevant bodies including the Alfred Hospital Ethics of Human Research Committee, Melbourne, Australia, in accordance with the Declaration of Helsinki (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond the application of pharmacotherapy, there is strong evidence, including a Cochrane review of the literature, that more intensive and structured management in the primary care setting will significantly improve BP control rates . We therefore conducted the multicenter, randomized Valsartan Intensified Primary Care Reduction of Blood Pressure (VIPER‐BP) study to test the clinical effectiveness and overall safety of a more intensive and structured approach to optimizing BP control in a group of individuals with persistently high BP levels in primary care. During the randomized component of comparing the VIPER‐BP intervention (n=1038) with an enhanced form of usual care (n=524), the primary endpoint (individual risk‐based BP target) was achieved in 36.2% vs 27.4% of participants, respectively (adjusted relative risk 1.28 in favor of the intervention; P =.001) and the classical BP target of ≤140/90 mm Hg in 63.5% vs 54.0% of participants (adjusted relative risk 1.18 in favor of the intervention; P <.001) .…”
mentioning
confidence: 99%
“…This is possibly reflected in the less favourable outcomes for blood pressure control, a common problem locally and worldwide. For example, the Valsartan Intensified Primary carE Reduction of Blood Pressure (VIPER‐BP) study, which involved more than 2300 primary care patients around Australia, showed that only 28% of ‘usual care’ patients met ideal blood pressure targets . Remoteness, with its inherent logistic challenges, may be a key factor in this context.…”
Section: Discussionmentioning
confidence: 99%
“…(18) Coordinating management of hypertension through primary healthcare initiatives represents an important, but often, under-estimated component of wider BP control. (19) At the other end of the spectrum (i.e. from treating hypertension as a primary risk factor), in the past, there have been similar issues in determining optimal ways to detect and manage the syndrome of chronic HF (CHF) in the ageing populations of high-income countries.…”
Section: Introductionmentioning
confidence: 99%